TEKNOLOGI GERABAH SITUS RANU BETHOK DAN RANU GRATI: “SEBUAH KAJIAN BERDASARKAN ANALISIS PETROGRAFI” - Gunadi Kasnowihardjo (Berkala Arkeologi, 2012)
Petrographic analysis is able to explain about the technology of pottery making, where the pottery come from and how to the pottery spread out. Petrographic analysis of sherds found either from the surface survey and excavations in the region of Bethok and Grati Lakes, can indicate whether the pottery found at the sites above have similar elements with the pottery marketed in the local market nowadays?. Based on the results of petrographic analysis can be concluded that the fragments of pottery found at both sites above have similar material elements of pottery now found in the local markets. Thus since long time ago pottery marketing from Besuk village production have reached the regional Tiris market within about 50 Km. Similarly, the pottery artefacts found at the Grati Lake are assumed to have originated from Keraton village production around 50 Km from the site.